In the Two Floors of the Tower : Sculpture 22 - Art Focus Contemporary Israeli Art, Jerusalem 1994 (Tel Aviv : The Tower Gallery, 1994)
Adani, Aharon ; Borenstein, Abraham ; Golani, Irene ; Yamburg, Aryhe ; Broek, Orna ; Fink, Berny ; Fine, David ; Neeman, Danny ; Amitai, Dove ; Wortman, Daniella ; Krischer, Zeev ; Ohela, Tal ; Sapir, Yaron ; Meron, Yigal ; Grinblat, Joram ; Levy, Moshe ; Meller, Moti ; Saul, Salo ; Massad, Anat ; Orion, Ezra ; Ben-Gal, Pnina
In the Two Floors of the Tower : Sculpture 22, The Tower Gallery, Tel Aviv, October - November - December 94. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek